Secularism and its critics - Bhargava, Rajeev (New Delhi ; New York : Oxford University Press, 1998)
With special reference to India.
Includes bibliographical references (p. [543]-550).
Keywords: Secularism -- India; Religion and state -- India; India -- Religion